Pengaruh Kepercayaan dan Promosi terhadap Minat Beli Ulang di E-Commerce Tokopedia pada Mahasiswa Universitas Mulawarman - Andra Rochmany (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to examine the influence of trust and promotions on repurchase intention on the Tokopedia e-commerce platform among students of Mulawarman University. E-commerce is increasingly becoming the primary platform for buying and selling activities, and understanding the factors that influence repurchase intention is crucial for business sustainability. Trust and promotions are two key variables believed to significantly shape consumer behavior. This research employs a quantitative method by distributing questionnaires to 100 Mulawarman University students who have previously shopped on Tokopedia. The collected data were analyzed using multiple linear regression techniques to test theinfluence of trust and promotions on repurchase intention. The analysis results indicate that both trust and promotions significantly influence repurchase intention on Tokopedia. Trust is found to be the most dominant factor, followed by promotions, which also have a positive impact. These findings imply that increasing trust through secure transactions, reliable products, and responsive customer service, along with effective promotional strategies, can enhance consumers' repurchase intention. This study provides practical contributions for Tokopedia management in designing strategies to maintain and increase repurchase intention among students. Additionally, it offers theoretical insights for further research on consumer behavior in e-commerce platforms